Mappings of terminal continua - Janusz J. Charatonik (International Journal of Mathematics and Mathematical Sciences)
The concept of a terminal continuum introduced in 1973 by G. R. Gordh Jr., for hereditarily unicoherent continua is extended to arbitrary continua. Mapping properties of these two concepts are investigated. Especially the invariance of terminality under mappings satisfying some special conditions is studied. In particular, we conclude that the invariance holds for atomic mappings.